Democracy and Civic Disobedience - Černevičiūtė, Jūratė (Problemos, 2006)
The article overviews issues of current discussions among the contemporary philosophers of law on the problem of civic disobedience in a democratic state. This discussion embraces different civic disobedience practices review from ancient times to contemporary democratic states. The next topic of discussions is a relationship between the general understandings of law as a concept: the place of morality and human rights in law and role of this understanding in justification of civic disobedience. The author concludes that in contemporary political theory civic disobedience is most important as a means of political justice and acceptance of the pluralism of values in liberal democracy.